New strategies for the synthesis and functionalization of tetrahydroxanthones. Issue 50 (16th December 2015) - Turner, Penelope A.; Samiullah,; Geden, Joanna V.; White, Alexander; Clarkson, Guy J.; Shipman, Michael
Abstract: Two strategies for the functionalization of simple tetrahydroxanthones (THX) on either of the carbocyclic rings are reported. By application of palladium catalysis, concomitant assembly of this heterocyclic scaffold with controlled introduction of substituents on the aromatic ring at C-5, C-6 or C-7 can be achieved. Variation in the nature of the added carbon fragment (aryl, alkenyl and alkynyl) is explored through use of different cross-coupling partners. Separately, functionalization at C-4 of the saturated carbocyclic ring is demonstrated through use of the extended enolate derived from 1-hydroxytetrahydroxanthone. Graphical abstract: